Niemieccy okupanci w Warszawie a jawność Holokaustu - Lehnstaedt, Stephan (Zagłada Żydów. Studia i Materiały, 2016)
In several last years there have been many publications concerning the knowledge and attitudes of Germans in relation to the Holocaust. The author deals with the issue what the civilian population and the military troops stationed at that time in Warsaw knew about the Holocaust. The occupants quickly learned about the massacres of Jews. Precise information spread at a rapid pace, and consequently each of the occupants was well informed of the Holocaust. Very few Germans stationing in Warsaw condemned crimes committed against the Jews. There was consensus on the need of extermination of Jews, some reservations aroused only form in which the genocide was carrying on. Open violence intertwined with its general acceptance, which led to a progressive callousness.